2020
DOI: 10.54045/ecie.v1i1.39
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Media Pembelajaran Bigbook Terhadap Kemampuan Menyimak Anak Tk Al-Wathaniyah Kecamatan Kota Timur Kota Gorontalo

Abstract: Tujuan Penelitian ini yaitu ingin mengetahui apakah ada pengaruh media pembelajaran bigbook terhadap kemampuan menyimak anak. Penelitian ini menggunakan jenis penelitian eksperimen dengan menggunakan pendekatan kuantitatif untuk mendapatkan informasi yang lengkap dan mendalam mengenai pengaruh media pembelajaran bigbook terhadap kemampuan menyimak anak pada kelompok A TK Al- wathaniyah kecamatan kota timur kota gorontalo. Populasi dalam penelitian ini berjumlah 18 sehingga penelitian ini dikatakan sebagai pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…By using the Big Book media, when reading, children will get used to predict the next word that will appear by remembering how the series of letters can become a word so that it can improve children's ability to read (Latifah, 2020). The results of a study conducted by Arsyad and Kuku (2020), found that the use of Big Book media provides a shared reading experience that is known in large forms for children's early reading stages because it is based on the belief that children who have experience before entering Kindergarten and based on beliefs That the children's selfconfidence and enthusiasm for reading must be raised when children learn to read.…”
Section: Discussionmentioning
confidence: 99%
“…By using the Big Book media, when reading, children will get used to predict the next word that will appear by remembering how the series of letters can become a word so that it can improve children's ability to read (Latifah, 2020). The results of a study conducted by Arsyad and Kuku (2020), found that the use of Big Book media provides a shared reading experience that is known in large forms for children's early reading stages because it is based on the belief that children who have experience before entering Kindergarten and based on beliefs That the children's selfconfidence and enthusiasm for reading must be raised when children learn to read.…”
Section: Discussionmentioning
confidence: 99%